2023 7th IEEE Electron Devices Technology &Amp; Manufacturing Conference (EDTM) 2023
DOI: 10.1109/edtm55494.2023.10103055
|View full text |Cite
|
Sign up to set email alerts
|

A new back-to-back graded AlGaN barrier for complementary integration technique based on GaN/AlGaN/GaN platform

Abstract: A novel composite barrier layer with back-to-back graded AlGaN in a GaN/AlGaN/GaN epitaxial structure for high performance n-and p-channel devices on the same platform is proposed. By adjusting the relative thicknesses of the two graded layers, we obtain a spread in the width and concentration of carriers in the 3D slabs. The best barrier amongst those studied, enhances the oncurrent ( 𝐼 !" ) by 24.4% in low voltage n-channel devices , 32.2% the p-channel devices whereas the figure of merit of the power devic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…The maximum degradation of I ON observed is ∼30%. Furthermore, we have shown that the figure of merit (FOM = V BV 2 /R on, sp ) can be improved by 3 times in a GaN power HEMT with the back-to-back graded AlGaN compared to the one with a conventional Al 0.25 Ga 0.75 N. 35 The impact of gate length scaling is investigated at Figure 4d demonstrates a comparison of the current density distribution from a u-GaN channel to the AlGaN barrier under the gate region (I Den. Gate ) and the access region between the gate and drain (I Den.…”
Section: ■ Methodologymentioning
confidence: 95%
“…The maximum degradation of I ON observed is ∼30%. Furthermore, we have shown that the figure of merit (FOM = V BV 2 /R on, sp ) can be improved by 3 times in a GaN power HEMT with the back-to-back graded AlGaN compared to the one with a conventional Al 0.25 Ga 0.75 N. 35 The impact of gate length scaling is investigated at Figure 4d demonstrates a comparison of the current density distribution from a u-GaN channel to the AlGaN barrier under the gate region (I Den. Gate ) and the access region between the gate and drain (I Den.…”
Section: ■ Methodologymentioning
confidence: 95%